Aldo-keto reductase 1B10 promotes development of cisplatin resistance in gastrointestinal cancer cells through down-regulating peroxisome proliferator-activated receptor-γ-dependent mechanism. (25th August 2016) - Matsunaga, Toshiyuki; Suzuki, Ayaka; Kezuka, Chihiro; Okumura, Naoko; Iguchi, Kazuhiro; Inoue, Ikuo; Soda, Midori; Endo, Satoshi; El-Kabbani, Ossama; Hara, Akira; Ikari, Akira
Abstract: Cisplatin ( cis -diamminedichloroplatinum, CDDP) is one of the most effective chemotherapeutic drugs that are used for treatment of patients with gastrointestinal cancer cells, but its continuous administration often evokes the development of chemoresistance. In this study, we investigated alterations in antioxidant molecules and functions using a newly established CDDP-resistant variant of gastric cancer MKN45 cells, and found that aldo-keto reductase 1B10 (AKR1B10) is significantly up-regulated with acquisition of the CDDP resistance. In the nonresistant MKN45 cells, the sensitivity to cytotoxic effect of CDDP was decreased and increased by overexpression and silencing of AKR1B10, respectively. In addition, the AKR1B10 overexpression markedly suppressed accumulation and cytotoxicity of 4-hydroxy-2-nonenal that is produced during lipid peroxidation by CDDP treatment, suggesting that the enzyme acts as a crucial factor for facilitation of the CDDP resistance through inhibiting induction of oxidative stress by the drug. Transient exposure to CDDP and induction of the CDDP resistance decreased expression of peroxisome proliferator-activated receptor-γ (PPARγ) in MKN45 and colon cancer LoVo cells. Additionally, overexpression of PPARγ in the cells elevated the sensitivity to the CDDP toxicity, which was further augmented by concomitant treatment with a PPARγ ligand rosiglitazone. Intriguingly, overexpression of AKR1B10 in the cells resulted in a decrease in PPARγ expression, which was recovered by addition of an AKR1B10 inhibitor oleanolic acid, inferring that PPARγ is a downstream target of AKR1B10-dependent mechanism underlying the CDDP resistance. Combined treatment with the AKR1B10 inhibitor and PPARγ ligand elevated the CDDP sensitivity, which was almost the same level as that in the parental cells. These results suggest that combined treatment with the AKR1B10 inhibitor and PPARγ ligand is an effective adjuvant therapy for overcoming CDDP resistance of gastrointestinal cancer cells. Graphical abstract: Highlights: AKR1B10 is up-regulated with CDDP resistance in gastrointestinal cancer cells. PPARγ is down-regulated in the CDDP-resistant cells. AKR1B10 detoxifies reactive aldehydes and suppresses PPARγ expression. Treatment with AKR1B10 inhibitor and PPARγ ligand overcomes the CDDP resistance.